The role of consumer-brand engagement in a digital marketing era - Bilro, Ricardo Jorge Godinho (2018)
The purpose of this thesis is to understand the role of consumer-brand engagement in a digital marketing era. We explore the consumer-brand engagement construct in relation to consumers as the engagement subjects, and brands (i.e., brand/companies) as the engagement objects. Our intention is to contribute to advancing the theoretical knowledge of this subject and to provide useful insights that can be used by practitioners, particularly companies that use interactive platforms to create consumer-brand relationships.